Deteksi Antibodi Imunoglobulin M dan Imunoglobulin G Anti Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) - Abdul-Hamid, Nur A; Wahongan, Greta J. P.; Tuda, Josef S. B. (JURNAL BIOMEDIK : JBM, 2021)
Abstract: COVID-19 is a disease caused by SARS-CoV-2 infection. Due to the increasing spread of COVID-19 infection in various countries, WHO declared the infection of COVID-19 as a pandemic situation. IgM and IgG antibodies test with the principle of immunochromatography is considered easier to perform than other test. The aims to detect anti SARS-CoV-2 IgM and IgG antibodies in North Sulawesi employees. This study is a descriptive study with cross sectional design. Antibody detection was carried out by dropping the serum of Balai Wilayah Sungai Sulawesi I's employees on the Clungene® COVID-19 IgG/IgM Rapid Test Cassette rapid diagnostic test based on antibody detected tool and interpreted based on the obtained result. As a result, tests which has been conducted on serum of 177 employees showed thirteen employees gave reactive results, where eight employees gave reactive IgM and IgG results, and five employees gave reactive IgG results. In conclusion, Immunoglobulin M and Immunoglobulin G were detected on some of Balai Wilayah Sungai Sulawesi I's employees.Keywords: COVID-19, SARS-CoV-2, IgM, IgG, immunochromatography  Abstrak: COVID-19 merupakan penyakit yang disebabkan oleh infeksi SARS-CoV-2. Oleh karena peningkatan penyebaran COVID-19 di berbagai negara, WHO mendeklarasikan infeksi COVID-19 sebagai situasi pandemi. Pemeriksaan antibodi IgM dan IgG dengan prinsip imunokromatografi dinilai lebih mudah dilakukan dibandingkan pemeriksaan lainnya. Penelitian ini bertujuan untuk mendeteksi antibodi IgM dan IgG anti SARS-CoV-2 pada karyawan kantoran Sulawesi Utara. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan desain penelitian cross-sectional. Deteksi antibodi dilakukan dengan meneteskan serum karyawan Balai Wilayah Sungai Sulawesi I pada kit rapid diagnostic test berbasis deteksi antibodi Clungene® COVID-19 IgG/IgM Rapid Test Cassette dan diinterpretasikan sesuai hasil yang didapat. Hasil yang diperoleh dari pemeriksaan yang dilakukan pada 177 serum karyawan menunjukan tiga belas karyawan memberikan hasil pemeriksaan reaktif, dimana delapan karyawan dengan hasil IgM dan IgG reaktif, serta lima karyawan dengan hasil IgG reaktif. Sebagai simpulan, antibodi Imunoglobulin M dan Imunoglobulin G anti SARS-CoV-2 terdeteksi pada karyawan Balai Wilayah Sungai Sulawesi I.Kata Kunci: COVID-19, SARS-CoV-2, IgM, IgG, imunokromatografi